ADIPOSITY SIGNIFICANTLY MODIFIES GENETIC RISK FOR DYSLIPIDEMIA. Issue 1 (10th December 2014) - Cole, CC; Nikpay, M; Lau, P; Stewart, AFR; Davies, RW; Wells, GA; Dent, R; McPherson, R
Abstract : Background: The Global Lipids Genetics Consortium identified 95 common loci that explained 12.2% (LDL-C), 12.1% (HDL-C) and 9.6% (triglycerides [TG]) of total variance in plasma lipid traits in the Framingham Heart Study. Since adiposity is associated with plasma levels of TG and HDL-C, we hypothesized that the predictive value of common risk variants for these lipid traits would differ for obese versus lean subjects. Methods: The study population consisted of two independent cohorts of subjects of European de-scent, genotyped on the Affymetrix 6.0 array with 1000G imputation. 1) OBLE: 959 obese/869 lean. 2) CC (healthy elderly subjects recruited as con-trols for a CAD study) 830 obese/1, 044 lean. A genetic predisposition score was calculated for each individual as a sum across SNPs of the number of risk alleles at that SNP multiplied by the effect size of the SNP. Results: In the OBLE cohort, a genetic risk score explained a greater percentage of the total TG variance in obese vs lean (beta GRS=0.154 mmol/L (p<2e-16) vs 0.094 mmol/L (p=5.8e-10); adjusted R2=0.090 vs 0.042), a finding that was replicated in the CC cohort for obese vs lean (beta GRS=0.153 mmol/L (p=1.5e-7) vs 0.102 mmol/L (p=4.2e-6); adjusted R2=0.044 vs 0.024). A similar but less significant trend was noted for LDL-C. In addition, the genetic risk score predicted variability in TG better than sex/age for obese subjects. In contrast a genetic risk score for HDL-C was a better predictor of this trait in lean versus obese subjects in both the OBLE and CC cohorts. Genetic risk scores for each lipid trait showed no association with BMI (P>0.2) indicating that the above findings are not due to possible overlap between genetic loci for BMI and lipid traits. Conclusions: Genetic predisposition to elevated plasma triglycerides and LDL-C and low HDL-C is highly sensitive to extremes of BMI.